Prevalence of Group B Streptococcus among Individuals in Yenagoa, Bayelsa State, South South, Nigeria - Patrick, Edafe Ejiro; Kenneth, Imarenezor Edobor Peter; Ifeoma, Anyiam Vivian; Akpomedaye, Salvage (Darul Yasin Al Sys, 2024)
Streptococcus agalactiae also known as Group B Streptococcus (GBS) is a Gram-positive bacterium that primarily colonizes the gastrointestinal and genitourinary tracts of humans. While it is a commensal organism in many healthy individuals, GBS can become pathogenic, causing a variety of infections. This study investigated the prevalence of Group B Streptococcus (GBS) colonization among adults in Yenagoa, Bayelsa State, Nigeria, to assess the distribution of GBS across various age groups and between sexes. A total of 185 individuals were included in the study which comprises of both male and female across different age groups (16–35 years). The specimens were cultured on Todd-Hewitt broth and Columbia Blood Agar. Morphological and biochemical tests, including Gram staining, CAMP test, and Hippurate Hydrolysis test, were performed to confirm the presence of GBS.Morphological analysis revealed small to medium-sized, grayish-white, beta-hemolytic colonies with characteristic cocci in pairs or chains, confirming Streptococcus agalactiae. The overall prevalence of GBS colonization was found to be 5.95%, with 5.17% in males and 6.30% in females. The highest prevalence was observed in the age group 31–35 years among females (16.00%) and in the 26–30 age group among males (9.09%). This study result provides essential baseline data on GBS prevalence among individuals in Yenagoa, highlighting the need for continued surveillance and targeted interventions in this area to reduce the risk of GBS transmission.